Comparing Pathways of Bradykinin Formation in Whole Blood From Healthy Volunteers and Patients With Hereditary Angioedema Due to C1 Inhibitor Deficiency - Charest-Morin, Xavier; Hébert, Jacques; Rivard, Georges-Étienne; Bonnefoy, Arnaud; Wagner, Eric; Marceau, François (Frontiers in Immunology, 2018)
Multiple pathways have been proposed to generate bradykinin (BK)-related peptides from blood. We applied various forms of activation to fresh blood obtained from 10 healthy subjects or 10 patients with hereditary angioedema (HAE, type I or II) to investigate kinin formation. An enzyme immunoassay for BK was applied to extracts of citrated blood incubated at 37°C under gentle agitation for 0-2 hrs in the presence of activators and/or inhibitory agents. Biologically active kinins in extracts were corroborated by c-Fos accumulation in HEK 293a cells that express either recombinant human B2 or B1 receptors (B2R, B1R). Biological evidence of HAE diagnostic and blood cell activation was also obtained. The angiotensin converting enzyme inhibitor enalaprilat, without any effect per se, increased immunoreactive BK (iBK) concentration under active stimulation of blood. Tissue kallikrein (KLK-1) and Kontact-APTT, a particulate material that activates the contact system, rapidly (5 min) and intensely (> 100 ng/mL) induced similar iBK generation in the blood of control or HAE subjects. Tissue plasminogen activator (tPA) slowly (≥ 1 hr) induced iBK generation in control blood, but more rapidly and intensely so in that of HAE patients. Effects of biotechnological inhibitors indicate that tPA recruits factor XIIa (FXIIa) and plasma kallikrein to generate iBK. KLK-1, independent of the contact system, is the only stimulus leading to an inconsistent B1R stimulation. Stimulating neutrophils or platelets did not generate iBK. In the HAE patients observed during remission, iBK formation capability coupled to B2R stimulation appears largely intact. However, a selective hypersensitivity to tPA in the blood of HAE patients suggests a role of plasmin-activated FXIIa in the development of attacks. Proposed pathways of kinin formation dependent on blood cell activation were not corroborated.